Does economic infrastructure promote economic development in Assam? A comparative study with India based on causality and cointegration approach - Patowary, Mridusmita; Baruah, Nayanmoni Borgohain (Asian Development Policy Review, 2025)
This study examines the impact of economic infrastructure and its sub-categories (Power, Rail, and Road) on economic development in Assam from 1990 to 2021, compared to India. The NITI Aayog recently released the SDG report 2023-24, revealing that Assam continues to lag behind other states and the national average in infrastructure development (SDG 9). We constructed the Economic Development Index and Economic Infrastructure Index using Principal Component Analysis (PCA). Johansen’s cointegration test and Vector Error Correction Model (VECM) were employed to examine long- and short-term relationships, with Gross Fixed Capital Formation and Population as control variables. Granger causality and Variance Decomposition Analysis further evaluated the direction and significance of effects. Results show that infrastructure positively affects development in Assam in the short and long-term, with a significant role from Gross Fixed Capital Formation. Granger causality confirms a two-way relationship, consistent with Wagner’s Law and endogenous growth theory for Assam, while India shows a stronger infrastructure impact. Economic infrastructure plays a critical role in Assam’s economic development, highlighting the need for targeted investments. Prioritizing infrastructure, especially Power and Rail, is essential for Assam’s sustainable development, helping it to align with national development standards.